2016
DOI: 10.1038/ncomms13151
|View full text |Cite
|
Sign up to set email alerts
|

TREM-1 links dyslipidemia to inflammation and lipid deposition in atherosclerosis

Abstract: Triggering receptor expressed on myeloid cells-1 (TREM-1) is a potent amplifier of pro-inflammatory innate immune responses, but its significance in non-infectious diseases remains unclear. Here, we demonstrate that TREM-1 promotes cardiovascular disease by exacerbating atherosclerosis. TREM-1 is expressed in advanced human atheromas and is highly upregulated under dyslipidemic conditions on circulating and on lesion-infiltrating myeloid cells in the Apoe−/− mouse model. TREM-1 strongly contributes to high-fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 71 publications
0
62
0
1
Order By: Relevance
“…Dyslipidemia is also associated with the increased expression of inflammatory mediator TREM-1 in advanced plaque (Zysset et al 2016). Further, increased TREM-1 expression is associated with unstable plaque and plaque vulnerability.…”
Section: Oxidized Low-density Lipoprotein (Oxldl)mentioning
confidence: 89%
See 2 more Smart Citations
“…Dyslipidemia is also associated with the increased expression of inflammatory mediator TREM-1 in advanced plaque (Zysset et al 2016). Further, increased TREM-1 expression is associated with unstable plaque and plaque vulnerability.…”
Section: Oxidized Low-density Lipoprotein (Oxldl)mentioning
confidence: 89%
“…Further, increased TREM-1 expression is associated with unstable plaque and plaque vulnerability. This suggests that dyslipidemia enhances the inflammation in plaque through increased surface expression of TREM-1 leading to increased monocytes homing, production of pro-atherogenic or pro-inflammatory cytokines, and foam cell formation, and thus enhanced the plaque vulnerability (Rai et al 2016;Rao et al 2016a;Zysset et al 2016) (Figures 2 and 3). Increased expression of TREM-1 on matured dendritic cells has been correlated with plaque instability (Rai et al 2016), and DCs and activated T cells have been (Figures 2 and 3).…”
Section: Oxidized Low-density Lipoprotein (Oxldl)mentioning
confidence: 99%
See 1 more Smart Citation
“…(5,6) The expression and function of TREM-1 has been indicated in various inflammatory diseases, including sepsis, cancer, retinopathy of prematurity (ROP), atherosclerosis, and experimental colitis. (7)(8)(9) Expression of TREM-1 in hepatic stellate cells was proposed as a prognostic factor in hepatitis B-related hepatocellular carcinoma (HCC), and TREM-1-mediated Kupffer cell activation was found in HCC. (10,11) Little is known about the role of TREM-1 in ALD.…”
mentioning
confidence: 99%
“…11 Moreover, recent evidence has linked TREM-1 to several non-infectious acute and chronic inflammatory diseases, including inflammatory bowel diseases, rheumatoid arthritis, psoriasis, atherosclerosis and cancer. [12][13][14] Noteworthy, in non-small cell lung cancer (NSCLC) patients the expression of TREM-1 by tumor-associated macrophages and the increase of the soluble TREM-1 in pleural effusions have been associated with tumor relapse and poor survival. 15 Recently, it has been demonstrated that TREM-1 is induced in dendritic cells undergoing hypoxia.…”
Section: Introductionmentioning
confidence: 99%